(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
In the present investigation planned to study the less explored sterculia gum as matrix carrier of Budesonide to colon. Developed the formulations from B1 to B4 contains alone sterculia gum and its proportion increased gradually in the formulation. The formulations B5 to B10 contain the sterculia gum in combination with Eudragit S 100 and the hydrophilic, hydrophobic polymer. The budesonide core in coat matrix tablets was prepared by direct compression method. The powder bed of the formulations is evaluated for pre compressional characteristics like bulk density, tapped density, compressibility index and angle of repose. The compressed budesonide core in coat matrix tablets were evaluated for post compressional characteristics like thickness, diameter, hardness, disintegration, friability and to understand the drug release pattern and to correlate the in vivo condition, the in vitro dissolution performed in three different gastro intestinal pH at 1.2, pH 7.4 and pH 6.8 with and without 4% rat cecal content. The in vitro dissolution results of formulations ascertain that sterculia gum alone in formulation uncontrolled the drug release in first 5 hrs and carried lesser amount of drug to colon. The formulations B8 in the first 5 hours released 4.3% and carried the larger amount of drug to colon and in absence of rat cecal content released 90% and in presences of 4% rat cecal content released 99% of drug, indicating the sterculia gum undergoes enzymatic degradation and this formulation is considered as potential in targeting the budesonide to colon in the local ulcerative colitis.